Appointment scheduling management in a healthcare system - Lee, Sarah Yu Zhen. (2011)
In the attempt to stay competitive, the healthcare service providers in Singapore are striving to improve the quality of service so as to earn the customers’ trust. One of the commonly know problem as observed by most healthcare service providers is the long waiting time that the patients have to undergo when seeking treatment. Thus in this project, the author aims to examine the effect of appointment scheduling management to the waiting time experienced by patients. The objective of this study is to look into the queuing models and simulation techniques and study the methodologies as adopted by past works, develop simulation models for analyzing the optimal number of patient intake and propose possible methods to improve the average waiting time. Software simulations are used in the study to model the utilization level on the operation process of a typical healthcare provider. With the inputs of parameters by assumptions, the simulation models are being constructed and results are generated for the analysis of the study. Comparison is then made on the different type of simulation models and the optimal number of patient intake to be about 60 to 65 and an average waiting time of 20 minutes is derived which can be used as a reference for future study. The study then concludes with the recommendations from the analysis and other factors to improve the service quality.